2017
DOI: 10.1007/s00181-017-1259-9
|View full text |Cite
|
Sign up to set email alerts
|

How school principals influence student learning

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 23 publications
1
39
0
2
Order By: Relevance
“…Miller (2013) warns against attributing all of the post-transition gains to the new principal. Had the original principal instead been retained, the pre-transition 1 However, Dhuey and Smith (2013a), studying principals in British Columbia, found that the same principal may have a larger contribution to student achievement if he or she is placed in a different school where the principal is a better "match" for the specific challenges that school faces. Also, Branch et al (2012) found that the impact of individual principals may vary more in schools with more low-income students, suggesting larger variation in match quality in these schools-although this finding could instead result from differences in the principals who lead these schools compared to schools with higher-income students.…”
Section: B Previous Researchmentioning
confidence: 99%
“…Miller (2013) warns against attributing all of the post-transition gains to the new principal. Had the original principal instead been retained, the pre-transition 1 However, Dhuey and Smith (2013a), studying principals in British Columbia, found that the same principal may have a larger contribution to student achievement if he or she is placed in a different school where the principal is a better "match" for the specific challenges that school faces. Also, Branch et al (2012) found that the impact of individual principals may vary more in schools with more low-income students, suggesting larger variation in match quality in these schools-although this finding could instead result from differences in the principals who lead these schools compared to schools with higher-income students.…”
Section: B Previous Researchmentioning
confidence: 99%
“…This notion has a long history in qualitative studies of effective schools (Purkey and Smith 1983). Some recent quantitative evidence indicates that school performance is higher when principals are more experienced (Clark, Martorell, and Rockoff 2009;Dhuey and Smith 2013), 1 have greater organizational management skills (Grissom and Loeb 2011), and demonstrate greater ability to recruit and retain high-quality teachers while removing low-quality teachers (Branch, Hanushek, and Rivkin 2012; Kalogrides, and Béteille 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dhuey and Smith (forthcoming) measure the cumulative effects of middle-school principals in British Columbia, Canada over three grade levels, finding a withinschool standard deviation of principal effectiveness that is 0.36 in math and 0.21 in reading. In a subsequent paper, Dhuey and Smith (2013) measure the effects of North Carolina principals, finding that principal-school match quality accounts for a significant portion of the variation in principal value added. Cannon, Figlio, and Sass (2012) also conclude that principal match quality matters, based on evidence from Florida that the persistence of a principal's value-added estimate declines when a principal changes schools.…”
Section: Introductionmentioning
confidence: 99%
“…The notion of a multiplicity of roles was best described by Md Ali (2015), who defined a principal as a leader, an administrator, and a leader in a school. A study by Dhuey and Smith (2018) suggested that a high-quality principal could influence student learning.…”
Section: Introductionmentioning
confidence: 99%